2013
DOI: 10.18573/j.2013.10244
|View full text |Cite
|
Sign up to set email alerts
|

Reporting consciousness in coma: media framing of neuro-scientific research, hope, and the response of families with relatives in vegetative and minimally conscious states

Abstract: This paper examines the public representation of, and family responses to, scientific studies into consciousness in coma-like states. We examine the publicity surrounding high-profile studies using functional Magnetic Resonance Imaging (fMRI) on ‘vegetative’ or ‘minimally conscious’ patients and compare this with family views. Our findings show how, with a few notable exceptions, the research was presented as an amazing breakthrough offering a potential ‘voice’ and choice for patients and hope and comfort for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 42 publications
0
34
0
1
Order By: Relevance
“…A study by Peters et al (2008) underlines the need for the inclusion of non-science and non-media actors, as there is the potential for “too much control by the scientific community of media coverage about it, as well as that for too much media influence on inner-scientific processes”, thereby positioning science-media interactions in a too positive light. The promotion of multi-directional communication between actors from science, social science, media, the public as well as other stakeholders has also consistently been advocated by others to avoid a misunderstanding of neuroscience, as well as an enhancement of scientific literacy (Illes et al 2010; Racine et al 2005; Samuel and Kitzinger 2013). …”
Section: Discussionmentioning
confidence: 99%
“…A study by Peters et al (2008) underlines the need for the inclusion of non-science and non-media actors, as there is the potential for “too much control by the scientific community of media coverage about it, as well as that for too much media influence on inner-scientific processes”, thereby positioning science-media interactions in a too positive light. The promotion of multi-directional communication between actors from science, social science, media, the public as well as other stakeholders has also consistently been advocated by others to avoid a misunderstanding of neuroscience, as well as an enhancement of scientific literacy (Illes et al 2010; Racine et al 2005; Samuel and Kitzinger 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The news article, which was published in the UK Mirror newspaper, was selected because of its sensationalist headline, large ‘visual’ section with pictures of brain scans, and main article which reported the study using mobilizations of hope, excitement and expectation. As part of a larger qualitative study which has been reported in Samuel and Kitzinger (2013), these same news items were presented to relatives of individuals with a severe brain injury in a series of interviews. We draw on some of the findings from these interviews to act as a comparison with the SPO interviews.…”
Section: Methodsmentioning
confidence: 99%
“…The study received wide media coverage, and scholars noted that the press release and news article presented optimistic portrayals using the language of ‘breakthrough’, with a focus on the benefits (Samuel and Kitzinger, 2013) (see Figure 1). Furthermore, during interviews conducted with individuals who have a relative with a severe brain injury, some interviewees also viewed the news article as overly optimistic: ‘ cause this [the fMRI news article] makes you think that you’re going to speak to them [severely brain-injured relative] through this magic machine ’ (interviewee) (Samuel and Kitzinger, 2013). In contrast, our SPO interviewees generally viewed the fMRI newspaper item as well written: ‘ I think this is quite good ’ (PO 10 media centre); and ‘ it does have caveats in there … saying it is early stages … I would have [been] happy with that one ’ (PO 4 research council).…”
Section: The Press Release As An Object Of Contested Visionmentioning
confidence: 99%
“…Some relatives of patients in VS and MCS express a certain ambivalence towards behavioural tools and brain imagining techniques [14] . The results of behavioural observations and imaging techniques are questioned, but along a number of different parameters.…”
Section: Understanding the Patientmentioning
confidence: 99%